1985
DOI: 10.1073/pnas.82.11.3863
|View full text |Cite
|
Sign up to set email alerts
|

Substituted benzamides as ligands for visualization of dopamine receptor binding in the human brain by positron emission tomography.

Abstract: Brain dopamine receptors mediate a number of biochemical and behavioral effects in experimental animals (1-4). Alterations of dopamine-receptor activity in the brain are in all probability related to some clinical manifestations of parkinsonism and the effects of neuroleptic drugs in schizophrenia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
110
0
3

Year Published

1986
1986
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 283 publications
(119 citation statements)
references
References 23 publications
6
110
0
3
Order By: Relevance
“…The reference method assumes that nonspecific binding of the tracer is equivalent in the striatum and reference region. Raclopride has been shown to have negligible nonspecific binding (Farde et al, 1985). We have demonstrated that this method is insensitive to changes in cerebral blood flow (Aston et al, 2000).…”
Section: Pet Proceduresmentioning
confidence: 83%
“…The reference method assumes that nonspecific binding of the tracer is equivalent in the striatum and reference region. Raclopride has been shown to have negligible nonspecific binding (Farde et al, 1985). We have demonstrated that this method is insensitive to changes in cerebral blood flow (Aston et al, 2000).…”
Section: Pet Proceduresmentioning
confidence: 83%
“…Research on the development of more spe cific Dz ligands has shown the potential of other series of dopamine antagonists, such as benzamide and ergolene analogues. Among the benzamides, raclopride was labeled with IIC and successfully used for the selective analysis by positron emission tomography (PET) of central Dz receptors in pri mates and humans (Farde et al, 1985). Among the ergolene derivatives, 2-bromolisuride (BLIS) has specific antidopaminergic properties.…”
Section: Discussionmentioning
confidence: 99%
“…11 C]SCH23390 (Halldin et al, 1986;Farde et al, 1987) and [ 11 C]raclopride (Farde et al, 1985;Köhler et al, 1985;Ito et al, 1998), respectively. The relative activity of cerebral aromatic L-amino acid decarboxylase (AADC) representing endogenous dopamine synthesis rate measured by 6-[…”
Section: Introductionmentioning
confidence: 99%